Efektivitas Peningkatan Keterampilan Membaca Pemahaman Peserta Didik Tingkat SMP Menggunakan Literation Educational Game - Rohmah, Naelur; Saputro, Sigit Dwi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research is motivated by the low reading skills of students. In this digital era, reading skills are very helpful for students in filtering the truth of information, managing information on social media, and thinking critically about the information received. The purpose of this study is to determine the effectiveness of the Literacy Educational Game media on reading comprehension skills for grade VIII students of SMPN 1 Kwanyar in the 2025 academic year. The method used is quantitative with a One Group Pretest-Posttest design. The data collection technique uses a multiple-choice test method. The test given to students contains indicators of literal understanding, reorganization, inferential understanding, evaluation, and appreciation. The results of the influence test using the paired t test obtained a significance of 0.00, which means there is an influence of the Literacy Educational Game media on reading comprehension skills. Strengthened by the results of the N-gain calculation, the score was able to reach 0.51 with a moderate category. The Literacy Educational Game media is proven to be effective in improving students’ reading comprehension skills.